Penerapan model pembelajaran mind mapping untuk meningkatkan ketrampilan membaca pemahaman siswa kelas III sekolah dasar - F H Lukluk, Karsono (Jurnal Pendidikan Dasar, 2020)
Abstract. The purpose of the study was to investigate the application of mind mapping models to improve reading comprehension skills of elementary school students. This research is Classroom Action Research with two cycles. The subjects of this research were students of the 3th students at SD Negeri Totosari Surakarta in the 2019/2020 academic year, totalling 30 students. This research uses data collection techniques in the form of interview, observation, field notes, tests, and documentation with data analysis of content validity and triangulation. This data was obtained from the pre-test and post-test results by applying the mind mapping learning model during the learning process. To conduct a statistical analysis of the study, using an assessment guideline adopted from one expert. The results show that the mind mapping learning model has a significant impact on improving reading comprehension skills of elementary school students. The findings of this study can provide a reference for teachers to apply mind mapping learning models into the learning process according to the material tobe developed.Keywords: Mind mapping,Reading chomprehensif , elementary school